Genotoxicity of Brosimum gaudichaudii measured by the Salmonella/microsome assay and chromosomal aberrations in CHO cells - Varanda, Eliana Aparecida [UNESP]; Pozetti, G. L.; Lourenco, M. V.; Vilegas, Wagner [UNESP]; Raddi, MSG (Elsevier B.V., 2002)
The root bark of Brosimum gaudichaudii Trecul (Moraceae) is popularly used for treatment of vitiligo. In the present study the mutagenic activity of the aqueous and methanolic extract as well as of the n-butanolic fraction of this medicinal plant were evaluated using Salmonella typhimurium assays, TA100, TA98, TA102 and TA97a strains, while the clastogenic effect in Chinese hamster ovary (CHO) cells in the G(1)/S, S and G(2)/S phases of the cell cycle. The results showed mutagenic activity of the aqueous extract against TA102 in the presence of S9, and of methanolic extract, with and without metabolic activation. TA100 mutagenicity was only observed for the methanolic extract in the absence of S9. The n-butanolic fraction did not present mutagenic activity. In CHO cells only the methanolic extract induced a significant increase of chromosomal aberrations in the G(1)/S and S phases, whereas a decrease in the mitotic index was observed in the G(1)/S and G(2)/S phases. No clastogenicity was observed for the aqueous extract. The furocoumarins (psoralen and bergapten) presented in the extracts might contribute to the mutagenicity. The lower activity of the aqueous extract was probably due to the presence of smaller amount of furocoumarins compared to the methanolic extract. (C) 2002 Elsevier B.V. Ireland Ltd. All rights reserved.
Keywords: Brosimum gaudichaudii Furocoumarins; Chinese hamster ovary cells; Salmonella typhimurium; mutagenic activity; chromosomal aberrations